If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(4d + -3) = 8d + -36 Reorder the terms: 4(-3 + 4d) = 8d + -36 (-3 * 4 + 4d * 4) = 8d + -36 (-12 + 16d) = 8d + -36 Reorder the terms: -12 + 16d = -36 + 8d Solving -12 + 16d = -36 + 8d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-8d' to each side of the equation. -12 + 16d + -8d = -36 + 8d + -8d Combine like terms: 16d + -8d = 8d -12 + 8d = -36 + 8d + -8d Combine like terms: 8d + -8d = 0 -12 + 8d = -36 + 0 -12 + 8d = -36 Add '12' to each side of the equation. -12 + 12 + 8d = -36 + 12 Combine like terms: -12 + 12 = 0 0 + 8d = -36 + 12 8d = -36 + 12 Combine like terms: -36 + 12 = -24 8d = -24 Divide each side by '8'. d = -3 Simplifying d = -3
| (10a)/(5a^5*5) | | 3x-6=-x-6 | | 4=H | | 6(4-x)=5 | | y/6=-29 | | 7x-5x+x-3+4x= | | 10x-10+2=-20 | | X/3-9=8 | | 9z(3m+5r)= | | 23=2y-17 | | X-7+2x=43 | | 174+(84*x)=1350 | | -(z-8)= | | 6.4x-4+x-1.9= | | -16x+5x=4(3x+7) | | 8+4=20 | | 7(x+33)+9=5(x-2)-3x | | 2t^2-2t+6=0 | | 22n-36=0 | | X^2-1.4x+0.49=0.35 | | 2m+13=16 | | 3(x-2)+5(x-2)=15x | | 3(5x+2)=2(3-6) | | m+17=34 | | 10x-10+2=-26 | | 3x+53=6x-35 | | 4/7x=11/x-3 | | m+17=134 | | 5x-48=-x | | -10y-3y-7=-12 | | 43x=8-4y | | 2c+22=7c-10 |